Oxidation of Arabidopsis thaliana COX19 Using the Combined Action of ERV1 and Glutathione - Flavien Zannini; Johannes M. Herrmann; Jérémy Couturier; Nicolas Rouhier (MDPI AG, 2023)
Protein import and oxidative folding within the intermembrane space (IMS) of mitochondria relies on the MIA40-ERV1 couple. The MIA40 oxidoreductase usually performs substrate recognition and oxidation and is then regenerated by the FAD-dependent oxidase ERV1. In most eukaryotes, both proteins are essential; however, MIA40 is dispensable in Arabidopsis thaliana. Previous complementation experiments have studied yeast mia40 mutants expressing a redox inactive, but import-competent versions of yeast Mia40 using A. thaliana ERV1 (AtERV1) suggest that AtERV1 catalyzes the oxidation of MIA40 substrates. We assessed the ability of both yeast and Arabidopsis MIA40 and ERV1 recombinant proteins to oxidize the apo-cytochrome reductase CCMH and the cytochrome c oxidase assembly protein COX19, a typical MIA40 substrate, in the presence or absence of glutathione, using in vitro cysteine alkylation and cytochrome c reduction assays. The presence of glutathione used at a physiological concentration and redox potential was sufficient to support the oxidation of COX19 by AtERV1, providing a likely explanation for why MIA40 is not essential for the import and oxidative folding of IMS-located proteins in Arabidopsis. The results point to fundamental biochemical differences between Arabidopsis and yeast ERV1 in catalyzing protein oxidation.